IMPLEMENTASI PERATURAN DAERAH KABUPATEN BULUKUMBA NOMOR 06 TAHUN 2003 TENTANG PANDAI BACA AL-QUR’AN BAGI CALON PENGANTIN - MUSTARI MUSTARI; A Nurauliah M (SUPREMASI: Jurnal Pemikiran, Penelitian Ilmu-ilmu Sosial, Hukum dan Pengajarannya, 2018)
This study aims to determine, Bulukumba Implementation Regional Regulation No. 6 of 2003 on the Smart Read Quran for the bride and groom in the District KUA Bulukumpa Bulukumba, and civil servants amounted to 3 people in the District Office of Religious Affairs Bulukumpa, to achieve the purpose the researchers used data collection techniques through a qualitative description, documentation, observation, and interviews. Data obtained from the results of the study were processed using qualitative analysis to determine Bulukumba Implementation Regional Regulation No. 6 of 2003 on intelligent read the Qur'an For the bride and groom. In the District KUA Bulukumpa.Hasil research shows that, in the District KUA Bulukumpa in implementing Bulukumba District Regulation No. 6 of 2003 on intelligent read the Qur'an for the bride, include: (1) the implementation of these regulations No. 6 of 2003 on clever read the Qur'an for the bride and groom are still held at KUA in District Bulukumpa, (2) factors supporting the implementation of regional legislation no 6 of 2003 in the Qur'an reading test in the Office of Religious Affairs in the District Bulukumpa Bulukumba.